(3QSGdI HGdaGQSjIs
(3ChdgG (B:s
(3ebShe Ydjg eG bHd BNQ ebShe hGbY s
(3BNQgG (B:s
(3hbGFe heGFd MGUd VQH bGYOg EQJaGY hJeJ gPg GdQSGdI HYhf Gddg hMSf GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3QSGdI ecJhHI HGdaGQSjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs